Pertanggungjawaban Pidana Bagi Orang Tua Pelaku Eksploitasi Anak Untuk Konten Media Sosial - Roudetul Jennah; Nur Azizah Hidayat (Universitas Merdeka Madiun, 2022)
Abstract— In this digital era, the influence of social media on people's lives is increasingly unstoppable. In fact, due to economic factors, more and more parents are exploiting their children for social media content. Children are heirs to the future of the nation and state whose dignity and worth as well as devoting their lives must be preserved. Exploitation of children for social media content is a crime, if this happens then there must be a party who is criminally responsible. The purpose of this study is to find out whether parents of child exploiters can be held criminally responsible and to find out the legal consequences and criminal liability for parents of child exploiters for social media content. This research is a normative juridical research with a statutory approach. From the results of the study, it can be seen that parents who exploit children for social media content can be subject to criminal liability as regulated in Law no. 35 of 2014 Amendments to Law Number 23 of 2002 concerning Child Protection and Law Number 11 of 2008 concerning Information and Electronic Transactions.